Pengawasan Penggunaan Air Tanah di Wilayah Perkotaan Kabupaten Sumedang - Wibawa, Gumbira Panji; Akadun, Akadun; Sudrajat, Arip Rahman (Universitas Medan Area, 2018)
In accordance with Regional Regulation Sumedang District No. 14 of 2011 on the Management of Ground Water, among which stated that every groundwater management must have a permit. However, in the implementation of violations of the rules and the weak enforcement of sanctions. Lack of public understanding of the importance of how good groundwater utilization is based on established rules is a constraint that leads to efforts to maintain the stability of groundwater availability. This can lead to more uncontrolled use of ground water. The objective of this research is to identify and study the monitoring of ground water usage in Sumedang District Urban Area. This research focuses on how the concept of monitoring the use of ground water. Through the method of description analysis, by recording interview data, observation and documentation obtained.